Oral Health Status Related to Daily Consumption of Sweets and Beverage Behaviors Among The Secondary School Students in Thayang District, Phetchaburi Province. - วะชังเงิน พายัพ; ทับศรีนวล ชมนาด (Thai Dental Public Health Journal, 2008)
Oral Health status were surveyed to review the situational background of daily consumption of foods and beverage among the students in secondary-level schools in Thayang district, Phetchaburi Province. The 312 samples were randomly chosen by multi-stages statistical methodology, standard oral-examination form, items of eating and drinking the pervasive beverage were included in the questionnaires and carefully prepared and significantly tested. The data were consolidated and analyzed to give out basic descriptive ; percentage, mean, standard deviation, and Chi-square significant test, the Pearson’s correlation coefficient, one way analysis of variance. T-test and pair comparative mean of Scheffe. The result of the study showed that 55.4% of the secondary-education level students are female, 26.6% of their parents’ occupations are government officers, state enterprise employee and the fixed income retired. Their parents’ monthly income is higher than 15,000 baht. The average daily allowance is 69 baht. The study found that DMFT is more than 5 teeth per person. More than 50% of the students afflicted with gingivitis. More than 70% of them preferred favored milk. Candies and jelly were the most preferable snacks. There were 79% students reported that they consumed candies and / or jelly in last 24 hours. The DMFT is significantly higher in students consumed candies and sugary biscuit than those who consumed ice-cream at p=0.03. The DMFT score in male was also significantly higher than female.